Α-Mangostin Improves Glucose Uptake and Inhibits Adipocytes Differentiation in 3T3-L1 Cells via PPARγ, GLUT4, and Leptin Expressions. (22nd March 2015) - Taher, Muhammad; Mohamed Amiroudine, Mohamed Zaffar Ali; Tengku Zakaria, Tengku Muhamad Faris Syafiq; Susanti, Deny; Ichwan, Solachuddin J. A.; Kaderi, Mohd Arifin; Ahmed, Qamar Uddin; Zakaria, Zainul Amiruddin
Abstract : Obesity has been often associated with the occurrence of cardiovascular diseases, type 2 diabetes, and cancer. The development of obesity is also accompanied by significant differentiation of preadipocytes into adipocytes. In this study, we investigated the activity of α -mangostin, a major xanthone component isolated from the stem bark of G. malaccensis, on glucose uptake and adipocyte differentiation of 3T3-L1 cells focusing on PPAR γ, GLUT4, and leptin expressions. α -Mangostin was found to inhibit cytoplasmic lipid accumulation and adipogenic differentiation. Cells treated with 50  μ M of α -mangostin reduced intracellular fat accumulation dose-dependently up to 44.4% relative to MDI-treated cells. Analyses of 2-deoxy-D-[ 3 H] glucose uptake activity showed that α -mangostin significantly improved the glucose uptake (P < 0.05 ) with highest activity found at 25  μ M. In addition, α -mangostin increased the amount of free fatty acids (FFA) released. The highest glycerol release level was observed at 50  μ M of α -mangostin. qRT-PCR analysis showed reduced lipid accumulation via inhibition of PPARγ gene expression. Induction of glucose uptake and free fatty acid release by α -mangostin were accompanied by increasing mRNA expression of GLUT4 and leptin . These evidences propose that α -mangostin might be possible candidate for the effective management of obesity in future.